Prevalence of demoralization and depressive symptoms in a sample of patients with supraventricular tachyarrhythmias: preliminary results - Accinni, Tommaso; Maraone, Annalisa; Bonucci, Alessio; D’Amato, Andrea; Lavalle, Carlo; Bersani, Francesco Saverio; Severino, Paolo; Pasquini, Massimo (Frontiers in Psychiatry, 2024)
Introduction Supraventricular tachyarrhythmias (ST) are the most common cardiac arrhythmias. Little is known about the potential impact of demoralization, which is considered as partially distinct from depression, on the course of ST. A correct assessment of both depressive symptoms and demoralization appears relevant for the treatment of these cardiac diseases, potentially influencing their course. Methods The sample consisted of 110 subjects affected by different ST, such as atrial fibrillation (AF), atrial flutter (AFL) and paroxysmal supraventricular tachycardia (PSVT). They all underwent a psychiatric evaluation; the Italian version of 9-item Patient Health Questionnaire (PHQ-9) and the Italian version of Demoralization Scale (DS) were administered. Descriptive statistics, pairwise comparisons, and correlational analysis have been implemented. Results 26 individuals (23.6%) presented high levels of demoralization. Of these, 20 (76.9%) had a diagnosis of AF and six patients (23.1%) received a diagnosis of other ST. No differences in demoralization levels resulted in regard of sex, cardiac diagnoses and anticoagulant therapies. Amongst people with high levels of demoralization, 13 (50%) received no formal psychiatric diagnosis, and 12 (46.2%) showed moderate/severe depressive symptoms. Demoralization levels and PHQ-9 scores showed a significant positive correlation in the whole sample (r=0.550, p<0.001). Discussion The present study found that in a sample of patients suffering from ST, high levels of demoralization were more frequent than clinically relevant depressive symptoms. We propose that demoralization and depression show partially distinguished psychopathological features, potentially associated with different therapeutic trajectories.